LATE VICTORIAN DISCOURSE IN THE CONTEXT OF LINGUISTIC AND CULTURAL STUDIES - Mariia Levishchenko (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2018)
The article deals with the analysis of the late Victorian discourse that influenced the choice of the following research methods: the content designations (the descriptive and receptive methods), data systematisation (the elements of the quantitative estimation method), visualisation (the schematic representation of elements of quantitative characteristics). It defines the late Victorian discourse as a cognitive-communicative continuum that is based on three parametrically relevant features: the sociocultural environment ("Victorian"), linguocultural modus ("English"), functional style ("Fictional"). In this context it is possible to distinguish the following characteristics for any textual array (both oral and written): 1) actualisation of a communicative axis built on the opposition of I / Other, which makes it possible to distinguish Itself in the discourse not just of its culture, but also delineate the boundaries of the self; 2) dialogue, manifested through the open character of an arbitrary communicative act, under which the author implies the interaction of I and the Other, even if the Other is a discourse (automotive communication, monologue, etc.); 3) polystylistics, i.e. a combination of elements of different styles (associated with the language pragmatics of the communicative act); 4) etiquette (speech etiquette, moral standards, etc.), i.e. the establishment of communicative patterns in the minds of native speakers. The late Victorian discourse appears to be an integral and harmonious part of the relevant cultural traditions that are correlated with speech ethic and a system of thoughtful speech actions associated with an offer, conformational and apologetic strategies. The communicative culture of the late Victorian discourse has a conventionalised nature and it is determined by the following principles: restraint, self-control, parity, mitigation.